Long-Acting Injectable Antipsychotic Treatment in Schizophrenia and Co-occurring Substance Use Disorders: A Systematic Review - Alexandria S. Coles; Dunja Knezevic; Tony P. George; Tony P. George; Christoph U. Correll; Christoph U. Correll; Christoph U. Correll; John M. Kane; John M. Kane; David Castle; David Castle (Frontiers in Psychiatry, 2021)
Objectives: Co-occurring substance use disorders (SUDs) among individuals with schizophrenia are a prevalent and complex psychiatric comorbidity, which is associated with increased symptom severity, worsened illness trajectory and high rates of treatment non-adherence. Recent evidence suggests that the use of long-acting injectable (LAI) antipsychotics may provide an effective treatment option for individuals with this dual-diagnosis.Methods: A systematic review of the literature was conducted using the databases PubMed, PsychInfo and Google Scholar for English-language studies, investigating the use of LAIs in co-occurring schizophrenia and substance use disorders (SCZ-SUDs).Results: Eight reports [one case study (n = 1), one case series (n = 8), three open-label retrospective studies (n = 75), and three randomized controlled trials (n = 273)] investigated the use of LAI antipsychotics in 357 participants with SCZ-SUDs [alcohol use disorder: 5 studies, n = 282; cocaine use disorder: 5 studies, n = 85; amphetamine use disorder: 1 study, n = 1; cannabis use disorder: 3 studies, n = 160; opioid use disorder: 3 studies, n = 19; methylenedioxymethamphetamine (MDMA) use disorder: 2 studies, n = 9; ketamine use disorder: 1 study, n = 4] and were included in this systematic review. Findings indicate significant improvements in substance use related outcomes across 7 of 8 studies, while in 6 of 8 studies, significant improvements in psychopathology-related outcomes were reported.Conclusions: LAI antipsychotics may be an efficacious intervention option for the treatment of SCZ-SUDs. However, varying methodological rigor, generally small sample sizes and heterogeneity of samples, settings, substances of abuse, tested LAIs and comparators, as well as psychosocial cotreatments and level of reported detail across studies requires that these findings be considered preliminary and interpreted with caution. Further research is required to better understand the effects of LAIs among individuals with SCZ-SUDs.